Penerapan HTB (Hierarchical Token Bucket) Dalam Manajemen Bandwidth - Rusli, Govi; Khairil, Khairil; Supardi, Reno (Jurnal Media Infotama, 2025)
SMA Negeri 5 South Bengkulu is one of the public schools in South Bengkulu that already has internet access at the school in collaboration with Indihome. The amount of bandwidth obtained is 50 mbps. The purpose of this research is to apply HTB (Hierarchical Token Bucket) in helping bandwidth management so that internet usage can be used evenly. The implementation of HTB (Hierarchical Token Bucket) in Bandwidth Management at SMA Negeri 5 South Bengkulu can help bandwidth management so that internet usage can be used evenly based on the priority user rights that have been created, where there are 3 bandwidth priorities that will be applied with different bandwidth amounts, namely the Principal, Teachers, and Staff. IP Address used is IP class C, where the Server has IP Address 192.168.1.15, then for clients connected to USB Lan Adapter has IP Address 192.168.2.2 for Principal, IP Address 192.168.2.3 for Teachers, and IP Address 192.168.2.4 for Staff. The implementation of this IP Address is carried out on every device that will be connected to the internet network at SMA Negeri 5 South Bengkulu. Based on the results of the tests that have been carried out, the results show that bandwidth management at SMA Negeri 5 South Bengkulu is running well and bandwidth distribution is carried out evenly.